(untitled) (Journal of Kidney Cancer, 2021)
Using a novel three-dimensional (3D) approach, we tracked histological changes to elucidate the earliest stages of renal clear cell neoplasia in normal kidney tissue of patients with von Hippel-Lindau (VHL) disease. Tissue blocks of interest were procured, serially sectioned, and 3D reconstruction of the entirety of pathologic events was performed. The results reveal an abundance of foci with aberrant clear cell proliferation that initially develop along the tubular lining, but have the potential to aggregate within individual tubules. This stage is followed by the extension of clear cell aggregates beyond the tubular basement membrane, which allows for the recruitment of angiogenesis derived from interstitial vasculature. The results suggest that the most frequent pathologic event in VHL kidneys is the presence of isolated or aggregated clear cells within the tubular epithelium, potentially developing further into a protracted process of neoplasia. The abundance of independent pathologic events in VHL kidneys confirms developmental mechanisms to precede tumor initiation. To our knowledge, this is the first report demonstrating that tracking of histologic changes in the 3rd dimension enables the confirmation of the sequence of events from the earliest pathologic change in the VHL kidney to the neoplastic stage. This approach is not only useful for visualization and quantification of pathologic changes but also for targeted sampling allowing selective analysis of the earliest stages of clear cell carcinogenesis.